Análise prognóstica de uma coorte pediátrica em portadores de nefropatia por IgA, através da Classificação de Oxford - Rafaela Cabral Goncalves Fabiano (2015)
IgA nephropathy (IgAN) is the most common glomerulonephritis worldwide. IgAN is characterized by a highly variable course ranging from a totally benign condition to end-stage renal disease (ESRD), although a rapidly progressive course in uncommon. As IgAN disease has an insidious progression, searches look for prognostic markers capable of predicting the IgAN outcome. Baseline renal function, arterial pressure, proteinuria and reduction in proteinuria during follow are some of the identified clinical markers. Several histological classification systems had been proposed to predict the outcome of IgAN; however, none has been widely accepted, especially by the lack of reproducibility studies. In 2009, the new Oxford Classification was published, based on high reproducibility and predictive power of the lesions, independent of clinical variables. The new Oxford Classification identified four histological features, capable of predicting renal outcome (ESKD or 50% reduction in eGFR at baseline): mesangial hypercellularity (M), endocapillary proliferation (E), segmental sclerosis or adhesion (S) and tubular atrophy/interstitial fibrosis (T). However, the application of this classification in other populations, especially paediatric, needs to be validated. This work aims to study the application of these variables as risk predictors in a South American pediatric cohort. This study included 56 patients with renal biopsy diagnosis of IgAN made with less than 18 years old, from 1982 to 2010. Clinical variables were determined, such as proteinuria, hypertension and glomerular filtration rate. In addition to the clinical features, histology was evaluated in order to address the application of Oxford classification in our population. For each patient, the paraffin block was selected and new thin sections were cut for histopathological analysis of the renal material. The biopsy specimens were classified and standardized according to the Oxford classification, by a pathologist blinded to patient outcome at the time of scoring. The primary endpoint outcomes were the cumulative percentage of patients who had a 50% reduction in glomerular filtration rate (GFR) compared to baseline and the rate of renal decline. Over a follow-up of 88.5 ± 9.4 months, 8 children (14%) had a 50% reduction in baseline renal function and 5 (9%) developed chronic ESRD in 109.0 ± 84.7 months. In Kaplan Meier analysis, the presence of endocapillary hypercellularity and tubular atrophy/interstitial fibrosis > 25% were predictors of renal survival. The initial proteinuria was also a clinical predictor of poor renal outcome. In multivariate analysis by Cox regression, after adjusted for initial proteinuria, endocapillary hypercellularity (HR 21.6, 95% CI, 2.9 to 160.5; p 0.003) and segmental glomerulosclerosis (HR 8.2; 95% CI, 1.3 to 51.0; p 0.023) were shown to be independent risk markers. In multivariate linear regression, tubular atrophy/interstitial fibrosis and also endocapillary hypercellularity were also associated with renal prognosis.